2017
DOI: 10.21608/jacb.2017.38415
|View full text |Cite
|
Sign up to set email alerts
|

Gene Action for Several Important Traits in Some Promising Maize -Teosinte Hybrids Using Generation Mean Analysis

Abstract: Although the need for increased production of summer fodder is so keenly felt in Egypt, the plant breeders did not focused much of their attention to improv fodder teosinte as silage exchange for maize. In this study, an attempt was made in order to partition the genetic variance to its components for fodder traits through the evaluation of different generations (P1, P2, F1, F2, BC1, BC2) of the promising maize-teosinte crosses under two locations (El-Serw and Sids). The results indicated the presence of signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 4 publications
2
5
0
Order By: Relevance
“…The hybrid P2 x P3 was the highest mean value for crude fibers (41.99%). These results are in agreement with those obtained by Abdel-Aty et al, (2013), Ghazy (2016) and Sakr (2017).…”
Section: Table 3 Mean Performances Of Parents and Their Six F1supporting
confidence: 94%
See 3 more Smart Citations
“…The hybrid P2 x P3 was the highest mean value for crude fibers (41.99%). These results are in agreement with those obtained by Abdel-Aty et al, (2013), Ghazy (2016) and Sakr (2017).…”
Section: Table 3 Mean Performances Of Parents and Their Six F1supporting
confidence: 94%
“…These results indicated that non-additive genetic effects played a major role in the genetic expression of this trait, indicating that the hybridization program would be effective in improvement of this trait. Similar results were also found by Sakr (2017) .For the crude fiber %, carbohydrates and crude lipid% the additive genetic variance (σ 2 A) was higher than that non-additive genetic variance (σ 2 D).…”
Section: Proportion Contributionsupporting
confidence: 84%
See 2 more Smart Citations
“…Teosinte has the advantage of giving very high yields, due to profuse tillering capacity that is absent in fodder maize. In addition to the ability to give three cuts against one cut obtained from fodder maize (Sakr, 2017). In addition, maize-teosinte crosses like maize can be safely fed on at any stage of growth (Hassan et al, 2017).…”
Section: Introductionmentioning
confidence: 99%